2015
DOI: 10.1007/s11242-015-0465-1
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic Convection in a Porous Medium Under Temperature Modulation

Abstract: The work proposed by Vadász et al. (Transp Porous Media 103:279-294, 2014) motivated us to take up the problem of chaotic convection under temperature modulation for study. The analysis of buoyancy driven convection for moderate Prandtl number in a fluid saturated porous layer heated from below and subject to temperature modulation is presented. It has been investigated that a better combination of values of , δ and scaled Rayleigh number Ra provides a way for chaos. It is found that the temperature modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 60 publications
3
37
0
Order By: Relevance
“…(30) and (31), we can easily obtain the expressions for R 31 and R 32 . Now, applying the solvability condition for the existence of third order solution, we get the Ginzburg-Landau equation for the stationary mode of convection, with time-periodic coefficients, in the form…”
Section: Amplitude Equation For Stationary Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…(30) and (31), we can easily obtain the expressions for R 31 and R 32 . Now, applying the solvability condition for the existence of third order solution, we get the Ginzburg-Landau equation for the stationary mode of convection, with time-periodic coefficients, in the form…”
Section: Amplitude Equation For Stationary Instabilitymentioning
confidence: 99%
“…Recently, considering various convective flow models in porous medium [5][6][7], fluid layer [8][9][10] the phenomenon of heat or mass transfer investigated, where the concept of regulating either heat or mass transfer is missing. The temperature gradient can be achieved by time-dependent heating or cooling at the boundaries, the related problems have been investigated by Nield [11], Chhuon and Caltagirone [12], Rudraiah et al [13], Rudraiah and Malashetty [14], Caltagirone [15], Bhatia and Bhadauria [16,17], Bhadauria [18][19][20][21][22][23][24], Bhadauria and Suthar [25], Bhadauria and Srivastava [26], Bhadauria et al [27], Bhadauria and Kiran [28,29] and Kiran and Bhadauria [30].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the solution of the nonlinear coupled system of partial differential equations (13)- (14), we represent the stream function and temperature in the following Fourier series expressions [12,13,15]:…”
Section: Mathematical Solutionmentioning
confidence: 99%
“…Their results show that periodic solutions and chaotic solutions alternate as the value of the scaled Rayleigh number varies, when forced vibrations are present. Very recently Kiran and Bhadauria [13] have studied chaotic convection in a Newtonian fluid saturated porous medium under temperature modulation at the boundaries. They found that the effect of temperature modulation is to enhance the behavior of chaotic motion.…”
Section: Introductionmentioning
confidence: 99%
“…They investigated the onset of instability in a horizontal porous layer using a model for the nanofluid that incorporated particle Brownian motion and thermophoresis. Related studies with various assumptions on the geometry and flow structure have been made by [12][13][14][15]. In the last few decades, researchers have also investigated thermal instability in a horizontal nanofluid layer subject to an applied magnetic field [16,17].…”
Section: Introductionmentioning
confidence: 99%